HIV-1–Specific Immunodominant T-Cell Responses Drive the Dynamics of HIV-1 Recombination Following Superinfection - Zhang, Hui; Cao, Shuang; Gao, Yang; Sun, Xiao; Jiang, Fanming; Zhao, Bin; Ding, Haibo; Dong, Tao; Han, Xiaoxu; Shang, Hong (Frontiers in Immunology, 2022)
A series of HIV-1 CRF01_AE/CRF07_BC recombinants were previously found to have emerged gradually in a superinfected patient (patient LNA819). However, the extent to which T-cell responses influenced the development of these recombinants after superinfection is unclear. In this study, we undertook a recombination structure analysis of the gag, pol, and nef genes from longitudinal samples of patient LNA819. A total of 9 pol and 5 nef CRF01_AE/CRF07_BC recombinants were detected. The quasispecies makeup and the composition of the pol and nef gene recombinants changed continuously, suggestive of continuous evolution in vivo. T-cell responses targeting peptides of the primary strain and the recombination regions were screened. The results showed that Pol-LY10, Pol-RY9, and Nef-GL9 were the immunodominant epitopes. Pol-LY10 overlapped with the recombination breakpoints in multiple recombinants. For the LY10 epitope, escape from T-cell responses was mediated by both recombination with a CRF07_BC insertion carrying the T467E/T472V variants and T467N/T472V mutations originating in the CRF01_AE strain. In pol recombinants R8 and R9, the recombination breakpoints were located ~23 amino acids upstream of the RY9 epitope. The appearance of new recombination breakpoints harboring a CRF07_BC insertion carrying a R984K variant was associated with escape from RY9-specific T-cell responses. Although the Nef-GL9 epitope was located either within or 10~11 amino acids downstream of the recombination breakpoints, no variant of this epitope was observed in the nef recombinants. Instead, a F85V mutation originating in the CRF01_AE strain was the main immune escape mechanism. Understanding the cellular immune pressure on recombination is critical for monitoring the new circulating recombinant forms of HIV and designing epitope-based vaccines. Vaccines targeting antigens that are less likely to escape immune pressure by recombination and/or mutation are likely to be of benefit to patients with HIV-1.